Direct conversion of carbon nanofibers and nanotubes into diamond nanofibers and the subsequent growth of large-sized diamonds. Issue 5 (18th January 2019) - Narayan, J.; Bhaumik, A.; Sachan, R.; Haque, A.; Gupta, S.; Pant, P.
Abstract : We report a pulsed laser annealing method to convert carbon fibers and nanotubes into diamond fibers under ambient conditions. Abstract : We report a pulsed laser annealing method to convert carbon fibers and nanotubes into diamond fibers at ambient temperature and pressure in air. The conversion of carbon nanofibers and nanotubes into diamond nanofibers involves melting in a super undercooled state using nanosecond laser pulses, and quenching rapidly to convert into phase-pure diamond. The conversion process occurs at ambient temperature and pressure, and can be carried out in air. The structure of diamond fibers has been confirmed by selected-area electron diffraction in transmission electron microscopy, electron-back-scatter-diffraction in high-resolution scanning electron microscopy, all showing characteristic diffraction lines for the diamond structure. The bonding characteristics were determined by Raman spectroscopy with a strong peak near 1332 cm −1, and high-resolution electron-energy-loss spectroscopy in transmission electron microscopy with a characteristic peak at 292 eV for σ* for sp 3 bonding and the absence of π* for sp 2 bonding. The Raman peak at 1332 cm −1 downshifts to 1321 cm −1 for diamond nanofibers due to the phonon confinement in nanodiamonds. These laser-treated carbon fibers with diamond seeds are used to grow larger diamond crystallites further by using standard hot-filament chemical vapor deposition (HFCVD). We compare these results with those obtained without laser treating the carbon fibers. The details of diamond conversion and HFCVD growth are presented in this paper.